2016
DOI: 10.18632/oncotarget.8798
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of major histocompatibility complex class I in subtypes of breast cancer is associated with estrogen receptor and interferon signaling

Abstract: Tumor-infiltrating lymphocytes (TILs) in triple-negative breast cancer (TNBC) have a strong prognostic and predictive significance. However, the mechanism of TIL influx in TNBC is unclear. Expression of major histocompatibility complex class I (MHC I) on the tumor cell is essential for the effective killing of tumor by cytotoxic TILs. In our current study, human leukocyte antigen (HLA) expression was inversely correlated with estrogen receptor (ER) expression in normal and cancerous breast tissue and positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 27 publications
1
62
1
Order By: Relevance
“…As previously demonstrated, no correlation was noted between the total number of DNA mutations and CD8B gene expression (Figure 3(a), p = 0.054). 13 However, a statistically significant positive correlation was present between ADAR1 and CD8B gene expression levels (Figure 3(b), correlation coefficient = 0.264, p = 0.016). The total number of DNA mutations was not correlated with ADAR1 expression (p = 0.366).…”
Section: Analysis Of Tcga Datamentioning
confidence: 85%
See 1 more Smart Citation
“…As previously demonstrated, no correlation was noted between the total number of DNA mutations and CD8B gene expression (Figure 3(a), p = 0.054). 13 However, a statistically significant positive correlation was present between ADAR1 and CD8B gene expression levels (Figure 3(b), correlation coefficient = 0.264, p = 0.016). The total number of DNA mutations was not correlated with ADAR1 expression (p = 0.366).…”
Section: Analysis Of Tcga Datamentioning
confidence: 85%
“…7 We have previously studied the expression of human leukocyte antigen (HLA)-ABC and MxA, which is known to be induced by interferon signalling, in TNBC and have identified a significant correlation between TIL levels and HLA-ABC/MxA expression in tumour cells. 12,13 Despite evidence suggesting that ADAR1 expression in cancer tissue is associated with elevated interferon signalling, the prognostic significance and relationship between ADAR1 expression in cancer cells and TIL levels in TNBC have not yet been well evaluated. We examined ADAR1 expression using immunohistochemistry and analysed the clinicopathological characteristics, including TIL levels and expression of other interferon-related proteins, of high ADAR1-expressing TNBCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently also neurobiological processes of synaptogenesis have been shown to be dependent on HLA and non‐HLA molecules of the MHC . Till date, over 160 different diseases associated with MHC have been identified by candidate gene analyses, gene expression, and proteomic analyses, with genome‐wide association studies (GWAS), Immunochip, and phenome‐wide association studies (PheWAS) (Table ) . Importantly, in HLA‐associated diseases, population‐based variation in the frequencies of risk/protective alleles and haplotypes is significant and should be included in phenotype characterization of disease subgroups and interventional trials …”
Section: Hla and Disease Associationsmentioning
confidence: 99%
“…[50][51][52] Till date, over 160 different diseases associated with MHC have been identified by candidate gene analyses, gene expression, and proteomic analyses, with genome-wide association studies (GWAS), Immunochip, and phenome-wide association studies (PheWAS) ( Table 4). 29,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] Importantly, in HLA-associated diseases, population-based variation in the frequencies of risk/protective alleles and haplotypes is significant and should be included in phenotype characterization of disease subgroups and interventional trials. 69 We have challenged the drawbacks of the HLA-DRB1 imputation in combining GWA SNP results with the allele copy numbers of HLA-DRB1*01 determined by genomic quantitative polymerase chain reaction (PCR) as a priori candidate gene associated with the complex disease of coronary artery disease.…”
Section: Hla and Disease Associationsmentioning
confidence: 99%
“…Recent studies also showed that “there were more cases with high expressions of HLA-G in non-luminal than in luminal subtypes (of breast cancer)” [50] and that “HLA expression was inversely correlated with oestrogen receptor (ER) expression in normal and cancerous breast tissue” [51]. …”
Section: Triple-negative Breast Carcinoma In East Asiansmentioning
confidence: 99%